One came home - Timberlake, Amy, author (New York : Yearling, 2014)
In 1871 Wisconsin, thirteen-year-old Georgia sets out to find her sister Agatha, presumed dead when remains are found wearing the dress she was last seen in, and before the end of the year gains fame as a sharpshooter and foiler of counterfeiters.